제주 지역에서 발생한 급성 이완성 마비 증세로 진행된 엔테로바이러스 71감염 - 김승효(Seung Hyo Kim) (Annals of Child Neurology(구 대한소아신경학회지), 2012)
포진성 구협염은 발열과 후인두의 수포성 병변을 보이며 대부분 증상이 경미하고 일주일 이내에 저절로 회복된다. 엔테로바이러스 71에 의한 수족구병이나 포진성 구협염의 경우에는 뇌수막염, 뇌간뇌염, 급성 이완성 마비 등의 신경학적 합병증이 발생할 수 있다. 제주도에서는 최근까지도 엔테로바이러스 71 감염 후 급성 이완성 마비를 보인 사례에 대한 보고가 없었다. 저자는 포진성 구협염으로 발현하여 양측 하지의 이완성 마비 증상을 동반한 19개월 된 환아에 대하여 제주도에서 처음으로 엔테로바이러스 71 감염 (C4a)을 확진하였기에 문헌 고찰과 함께 보고하는 바이다. Most human enterovirus 71 (EV71) infections present with mild conditions such as hand. foot.mouth disease or herpangina. However, EV71 can invade the central nervous system, causing neurologic diseases such as brainstem encephalitis, meningitis and acute flaccid paralysis despite the near complete eradication of polioviruses. Neurological complications from EV71 infection occur within a few days and can lead to death even though rare. There is no report for EV71 infection with severe neurological manifestation in Jeju Island so far. We therefore report a case of EV 71 infection with bilateral acute flaccid paralysis for the first time in Jeju Island with review of related articles. KCI Citation Count: 2